Intellectual Capital Disclosure: Determining Factors and Their Impact on Company Value - Zulfa Rosharlianti; Novi Akhsani; Anisa Anisa (AIBPM Publisher, 2022)
Disclosure of intellectual capital in Indonesia is still voluntary, it has been implicitly regulated in PSAK No. 19. This study will examine the determinants of intellectual capital disclosure and its consequences on firm value. The determining factors that are thought to influence the disclosure of intellectual capital in Indonesia are listing age, firm size and industry of type. The impact of intellectual capital disclosure is the value of the company. The research population is all companies that are included in LQ45 on the Indonesia Stock Exchange in the period 2015 to 2020. The number of research samples is 132 observations. The analysis used is multiple linear regression. The results of this study indicate that Listing age affects intellectual capital disclosure, Firm size affects intellectual capital disclosure, Industry of type does not affect intellectual capital disclosure and Intellectual capital disclosure affects firm value. The implication of these findings is that companies are starting to realize the importance of the role of intellectual capital in creating a company's sustainable competitive advantage. Intellectual capital is an important resource in the information and knowledge era for company growth that companies need to disclose to investors and potential investors.